Effects of poloxamer 407‐induced hyperlipidemia on hepatic multidrug resistance protein 2 (Mrp2/Abcc2) and the pharmacokinetics of mycophenolic acid in rats. (September 2016) - Kwon, Mi Hye; Yoon, Ji Na; Baek, Yu Jin; Kim, Yu Chul; Cho, Yong Yeon; Kang, Hee Eun
Abstract: Hepatic multidrug resistance‐associated protein 2 (Mrp2) is responsible for the majority of the biliary elimination of endogenous and exogenous substances, therefore it is important to evaluate possible functional changes in Mrp2 activity under conditions of hyperlipidemia (HL). Thus, the present study assessed the protein expression and transporting activity of hepatic Mrp2 based on the in vivo biliary excretion of phenolsulfonphthalein (PSP) as a model anionic substrate for Mrp2 in poloxamer 407‐induced hyperlipidemic rats (HL rats) and compared these values with those for control rats. The pharmacokinetics of mycophenolic acid (MPA) and mycophenolic acid‐7‐ O ‐glucuronide (MPAG) were evaluated after the intravenous (5 mg/kg) and oral (10 mg/kg) administration of MPA to control and HL rats. In HL rats, the protein expression of hepatic Mrp2 and its biliary transporting activity exhibited significant reductions (by 24.3% and 24.6%, respectively) in the absence of a change in bile flow rate. Unexpectedly, HL and control rats showed comparable biliary excretion rates of MPAG due to the counter effects of the reduced expression and activity of Mrp2 and a 484% increase in the free fraction of MPAG in HL rats. The estimated biliary clearance value of free MPAG in HL rats was considerably slower (by 77.1%) than that in control rats. Although significant pharmacokinetic changes in total MPA and MPAG levels were not observed in HL rats, there was a marked increase in free MPA and MPAG levels. Clinically relevant pharmacokinetic changes in subjects with HL that are related to MRP2 could not be ruled out. Copyright © 2016 John Wiley & Sons, Ltd.